STRATEGI IMPLEMENTASI BUKU “BELAJAR BAHASA ARAB TERPADU” DALAM PEMBELAJARAN BAHASA ARAB DI SMP IT PELITA PROBOLINGGO - Yusfian, Firli Perdana; Fauji, Imam (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to analyze the strategy for implementing “Belajar Bahasa Arab Terpadu” books in Arabic language learning at Pelita Integrated Islamic Junior High School Probolinggo. The research method used is descriptive qualitative using observation, interviews and documentation as data collection techniques. Triangulation is used to test the validity of the data obtained. The results of the research show that teachers use various methods in teaching, such as the hiwar method for maharah kalam, the qiro'ah jahriyah and saamitah methods for maharah qiroah, the audio-lingual method for istima', and the drill method in maharah kitabah teaching. The supporting factor in this implementation is information technology (IT) support, while the inhibiting factor is the diversity of student backgrounds